2023
DOI: 10.1007/s00127-023-02438-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of the COVID-19 mental health international for the health professionals (COMET-HP) study: depression, suicidal tendencies and conspiracism

Abstract: Introduction The current study aimed to investigate the rates of anxiety, clinical depression, and suicidality and their changes in health professionals during the COVID-19 outbreak. Extended author information available on the last page of the article Materials and methodsThe data came from the larger COMET-G study. The study sample includes 12,792 health professionals from 40 countries (62.40% women aged 39.76 ± 11.70; 36.81% men aged 35.91 ± 11.00 and 0.78% non-binary gender aged 35.15 ± 13.03). Distress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 128 publications
(137 reference statements)
1
0
0
Order By: Relevance
“…Consequently, nurses have been found to have the highest rates of clinical depression among healthcare personnel, indicating a serious challenge to their well-being. 57 This study supports the view that the increased concern about contagion during the COVID-19 pandemic has led to increased stress levels among nurses, as suggested by previous research. 58 Similarly, other studies have reported high levels of stress, anxiety, and depression among nurses concerned about contracting the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, nurses have been found to have the highest rates of clinical depression among healthcare personnel, indicating a serious challenge to their well-being. 57 This study supports the view that the increased concern about contagion during the COVID-19 pandemic has led to increased stress levels among nurses, as suggested by previous research. 58 Similarly, other studies have reported high levels of stress, anxiety, and depression among nurses concerned about contracting the virus.…”
Section: Discussionsupporting
confidence: 90%